Seasonal activities, morphological characteristics, and veterinary importance of Haemaphysalis mageshimaensis in Ishigaki and Yonaguni, Okinawa, Japan - Satoko Nakao; Thillaiampalam Sivakumar; Yuko Takakuwa; Hajime Suzuki; Keiichiro Ohta; Keiko Nakamura; Osamu Tsuha; Yuzuru Ikehara; Sanae Ikehara; Syota Ohki; Mizue Inumaru; Yukiko Higa; et al. (Ticks and Tick-Borne Diseases)
Ticks are of veterinary importance as they transmit various pathogens to animals. In Yaeyama, Okinawa, Japan, Haemaphysalis longicornis became the dominant tick species after the eradication of Rhipicephalus (Boophilus) microplus in the 1990s. However, any recent changes remained unclear due to lack of surveys. We surveyed questing ticks in pastures on Ishigaki and Yonaguni islands of Yaeyama, from September 2022 to May 2024. A total of 18,435 ticks, including 14,784 from Ishigaki and 3,651 from Yonaguni, were collected. The ticks collected in Ishigaki and Yonaguni included 7,637 and 2,697 larvae, 5,870 and 829 nymphs, and 1,277 and 125 adults, respectively. Morphological analysis classified all collected adults and nymphs as either Haemaphysalis mageshimaensis or H. longicornis. We observed that H. mageshimaensis was dominant in both Ishigaki and Yonaguni, accounting for 99 % and 96 % of the populations, respectively, compared to H. longicornis. While adults and nymphs of H. longicornis were active in spring, summer, and autumn, H. mageshimaensis was active year-round. We found that the differences in the body colour and length, density and number of hairs on the second palp segment, and degree of protrusion on the outer edge of the third palp segment may be useful for differentiating H. mageshimaensis from H. longicornis. PCR screening of DNAs from selected ticks showed that 9.7 % of H. mageshimaensis and 25 % of H. longicornis were infected with Theileria orientalis. Our findings indicate that H. mageshimaensis has overtaken H. longicornis as the dominant species in Yaeyama, highlighting the need for year-round tick control measures.